Importance of the decoration in shaped cobalt nanoparticles in the acceptor-less secondary alcohol dehydrogenation. Issue 15 (30th April 2020) - Kaźmierczak, Kamila; Ramamoorthy, Raj Kumar; Moisset, Arthur; Viau, Guillaume; Viola, Arnaud; Giraud, Marion; Peron, Jennifer; Sicard, Lorette; Piquemal, Jean-Yves; Besson, Michèle; Perret, Noémie; Michel, Carine
Abstract : Ligands matter for shaped decorated Co nanoparticles, at the frontier between homogeneous and heterogeneous catalysis. Abstract : Metal catalysts are essential in the production of fuels and chemicals. Nonetheless, tailoring the exposed active sites to achieve the maximal theoretical conversion is still a great challenge. In the case of structure-sensitive reactions, such as the attractive acceptor-less alcohol dehydrogenation, playing on the exposed metallic sites appears as an appealing strategy. Still, this approach requires advanced preparation protocols and is even more difficult to implement for supported non-noble metal catalysts which easily undergo sintering. Using the polyol method, we synthesized fourteen different cobalt catalysts, which consist of unsupported shaped nanoparticles stabilized by adsorbed carboxylate ligands. Their shape and the amount of ligands were characterized by combining TEM and TGA-N2 measurements. These catalysts were found to be active in the 2-octanol dehydrogenation conditionally upon an organic layer limited to 1 to 2 monolayers. Moreover, they were fully selective towards the desired ketone and H2 . The active catalysts were stable, with no leaching or modification of the shape during the reaction. Periodic DFT computations predict a greater activity of the pristine open-type facet than of the compact one, but this is not confirmed experimentally with no clear correlation between the activity expressed in turnover number and the amount of a given type of site as quantified by TEM. Further modeling including the organic layer shows that the presence of ligands reduces the sensitivity to the metallic structure. Nonetheless, these ligands generate a catalytic pocket, similar to the one found in enzymes, that interacts with the alcohol substrate through H-bonding. This pocket is the most adapted to the alcohol dehydrogenation on the open-type facet, which is mainly exposed on rods. This detailed understanding paves the way to an improved design of bespoke unsupported catalysts considering simultaneously the structure and the nature of the ligand.